Deconvolution of main hydration kinetic peaks in properly sulfated Portland cements with boundary nucleation and growth models and relation to early-age concrete strength development. (19th September 2022) - Pichler, Ch.; Perfler, L.; Lackner, R.
Abstract: When the hydration kinetics of properly sulfated Portland cements is monitored by heat flow calorimetry, the initial dissolution peak and the dormant period is followed by the main hydration peak – formation of calcium-silicate-hydrates and portlandite, the so-called silicate peak. This main peak is superimposed by a peak associated to further tricalcium aluminate dissolution and a surge in precipitation of sulfoaluminates (the so-called sulfate depletion peak) right after sulfate added for setting control is depleted in the material system. In this paper strategies for the deconvolution of silicate peak and sulfate depletion peak are presented. Hereby, the boundary nucleation and growth model and the classical bulk nucleation and growth model serve as tools for deconvolution of calorimetric data. We discuss obtained kinetic parameters and their temperature dependency. The boundary nucleation and growth model for constant nucleation rate emerged as the most suitable model for the silicate reaction, the bulk nucleation and growth model with an order of three, indicating site saturation, as adequate for the sulfate depletion peak. The reaction enthalpy for tricalcium silicate hydration was obtained as 503 J/g, remarkably close to literature values. Calorimetric data related to the sulfate depletion peak is corroborated by X-ray diffraction analysis of formation history of crystalline hydration products. Furthermore, the history of the (silicate) degree of reaction as predicted by the boundary nucleation and growth model for different temperature histories is related to experimentally obtained early-age strength histories. Graphical abstract: Highlights: Investigation of hydration kinetics of commercial, well-sulfated Portland cement. Main peak (C-S-H and portlandite formation) superimposed by sulfate depletion peak. Strategies for deconvolution of peaks with Avrami–Cahn models as tools for analysis. Degree of silicate reaction history is linked to early-age strength gain.